The Phenomenon of Early Marriage: A Case Study in Teluk Kuali Village, Tebo Ulu District, Tebo District, Jambi Province” - Wati, Nur Tria; Mutia Kahanna; Edi Satria (Kirana Publisher (KNPub), 2023)
This thesis is entitled “The Phenomenon of Early Marriage: A Case Study in Teluk Kuali Village, Tebo Ulu District, Tebo District, Jambi Province”. The purpose of this research is to describe Early Marriage, that is, there are factors that cause Early Marriage, these factors are also inherent in a person which causes social problems. The theory used in this thesis is the phenomenological theory of Alfred Schutz. The method that the author uses is a qualitative method, with data collection techniques namely observation, interviews and documentation. The requirement for a person to marry is when a woman reaches the age of 19 (nineteen) years, and for a man 19 (nineteen) years this is stated in the Law on Marriage. Early marriage is a marriage carried out by a pair of teenagers (boys and girls) who are less than 19 years old and immature physically and psychologically. The Impact of Early Marriage has positive and negative impacts, the positive impacts are becoming more independent, avoiding adultery, and reducing the burden on parents. Furthermore, it can also be seen from the side of the negative impact, namely, it often causes problems in the household, education, and a low economy.